Retroviral association with ovarian adenocarcinoma in laying hens. Issue 2 (4th March 2022) - Ramoutar, Varsha V.; Johnson, Yvette J.; Kohrt, Laura J.; Bahr, Janice M.; Iwai, Aya; Caporali, Evelyn H.G.; Myint, Maung S.; Szigetvari, Nicholas; Stewart, Matthew C.
ABSTRACT: The laying hen has been used as a model for ovarian adenocarcinoma (OAC) in women. Previous work has shown an association between expression of endogenous retroviral proteins and elevated envelope mRNA and occurrence of OAC in humans, but causality has not been demonstrated. The objective of this study was to determine whether there is a similar association between retrovirus presence and OAC in a commercial laying hen flock at the University of Illinois Poultry Research facility with a history of a high OAC prevalence in older hens. Laying hens of three age strata were randomly selected for a cross-sectional study. Blood samples were collected, and serum was tested for antigens of endogenous or exogenous avian leukosis virus (ALV) by ELISA. Birds were humanely euthanized, and spleens, ovaries, and any tissues with gross lesions were sampled. Ovaries and gross lesions were examined histologically and spleens were used for RT-PCR to detect endogenous ALV via ALV-E env mRNA expression. Overall, hens with OAC were 5.2 times more likely to be ALV positive than hens without OAC (95% C.I. 2.06–13.14). Controlled for age, OAC positive hens were 3.6 times more likely to be positive for ALV via antigen-capture ELISA (95% C.I. 1.08–11.96). Endogenous ALV-E in hens may be analogous to human endogenous retroviruses, which have also been associated with OAC in women. Further studies to establish causation are warranted to better understand the potential for laying hens to serve as a laboratory model for viral-induced ovarian tumours in humans. RESEARCH HIGHLIGHTS: OAC in hens was associated with age, seropositivity for ALV, and endogenous ALV mRNA expression. Older hens with OAC were more likely to be ALV seropositive by ELISA and ALV-E mRNA-positive. Associations between OAC, age, and endogenous retrovirus expression have been reported in humans. These findings support the use of hens as models for OAC in humans.